Priming With Red Blood Cells Allows Red Blood Cell Exchange for Sickle Cell Disease in Low-Weight Children - Hequet, Olivier; Boisson, Camille; Joly, Philippe; Revesz, Daniela; Kebaili, Kamila; Gauthier, Alexandra; Renoux, Celine; Creppy, Severine; Nader, Elie; Nicolas, Jean François; Berard, Frédéric; Cognasse, Fabrice; et al. (Frontiers in Medicine, 2021)
Red blood cell (RBC) exchanges (RCE) are frequently used to treat and prevent cerebrovascular complications in patients with sickle cell anemia (SCA). However, the low weight of young children represents serious concerns for this procedure. The Spectra Optia device can perform automatic priming using RBCs (RCE/RBC-primed) which could allow RCE to be performed in young children without hypovolemic complications, but this method requires evaluation. We prospectively analyzed the clinical safety of the RCE/RBC-primed procedure in 12 SCA low-weight children under either a chronic RCE program or emergency treatment over 65 sessions. We monitored grade 2 adverse events (AEs) such as decrease in blood pressure, increase in heart rate, fainting sensation or transfusion reactions and identified the critical times during the sessions in which AEs could occur. Post-apheresis hematocrit (Hct) and fraction of cell remaining (FCR) values were compared to the expected values. We also compared the impact of automatic RCE (n = 7) vs RCE/RBC-primed (n = 8) on blood viscosity and RBC rheology. A low incidence of complications was observed in the 65 RCE sessions with only 7 episodes of transient grade 2 AEs. Post-apheresis Hct and FCR reached expected values with the RCE/RBC-primed method. Both the automatic and priming procedures improved RBC deformability and decreased the sickling tendency during deoxygenation. Blood rheological features improved in both RCE/RBC-primed and automatic RCE without priming conditions. The RCE/RBC-primed procedure provides blood rheological benefits, and is safe and efficient to treat, notably in young SCA children in prophylactic programs or curatively when a SCA complication occurs.